The Impact of Merdeka Curriculum on Students’ Interest in Learning English - Zahwannisa, Riskha; Lubis, Yani (Institut Agama Islam Negeri Palopo, 2025)
The implementation of the Merdeka curriculum in SMA Negeri 1 Tanjung Balai has been running for several years. So this study aims to determine the implementation of the Merdeka curriculum in English subjects at SMA Negeri 1 Tanjung Balai. This study uses a descriptive qualitative research type. Data were obtained through interviews, observations, and documentation. Then analyzed by data collection, data condensation, data presentation, and conclusions. Based on the results of the study, the implementation of the Merdeka curriculum in English learning at SMA Negeri 1 Tanjung Balai has been implemented well. Teachers at SMA Negeri 1 Tanjung Balai have carried out thorough learning planning by analyzing student needs, compiling teaching modules, and participating in training related to the implementation of the Merdeka curriculum. In addition, teachers at SMA Negeri 1 Tanjung Balai have also used fun learning methods in implementing learning. Although several obstacles were found during the evaluation, these obstacles could be overcome so that the implementation of the Merdeka curriculum in English learning at SMA Negeri 1 Tanjung Balai could run well.